(untitled) (Journal of Legal Studies, 2018)
Legal profession has experienced substantial changes owing to economic needs and evolution of legal industry and market. This has multiplied the need of new breed of competent and well versed lawyers in the global legal profession. The character and calibre of the legal profession is determined by the quality and standard of law faculties and of legal education. The study intends to explore and compare the legal education and admission to practice in China, India and Pakistan. It further expounds the structure, purpose, teaching methods, pathways to admission and problems of legal education in all jurisdictions. The research contemplates on the distinctive features of legal education and its compatibility with practical aspect of legal profession in the selected countries. The study finds that China and Pakistan have a similar structure of mandatory training after graduation which India does not provide for. The study concludes that all jurisdictions must include legal practical course into their curriculum to be able to compete with the global demand.